A sustainable analysis of a detached house heating system throughout its life cycle. A case study - Sasnaskaitė, Violeta; Užšilaitytė, Lina; Rogoža, Artur (International Journal of Strategic Property Management, 2010)
Approximately 40% of final energy is consumed in buildings both in Lithuania and the European Union. In cold climate countries major part of the consumed energy is heat. Therefore, in order to build energy efficient buildings it is very important at the design stage to make a right decision regarding the choice of the heating system. The aim of the study is to compare three different heating systems from the point of view of a sustainable development concept. This paper summarizes results of the life cycle analysis, which has been made on the heating systems of an existing residential building. The purpose of this study is to define the primary energy consumption, CO2 emissions and investments necessary for the three different heating systems during their life span and to evaluate them applying a multicriteria approach. The systems under consideration are the heating systems comprising a standard cast‐iron gas boiler and steel radiators or a condensing gas boiler combined with floor heating or a condensing gas boiler combined with steel radiators. A life cycle assessment has been made for the life span of 80 years. As a final decision making criteria the 3E criteria is proposed.First published online: 18 Oct 2010